PENGARUH PENERAPAN METODE DEMONSTRASI DALAM PEMBELAJARAN BAHASA ARAB TERHADAP MOTIVASI SISWA KELAS VIII SMP PONDOK PESANTREN PUTRI UMMUL MUKMININ AISYIYAH WILAYAH SULAWESI SELATAN - Hajrah Hajrah; Abd. Rahim Razaq (Al-Maraji' : Jurnal Pendidikan Bahasa Arab, 2018)
This study aims to determine the effect of the demonstration method on the motivation to learn Arabic in the eighth-grade students of Ummul Mukminin Islamic Boarding School of Aisyiyah in South Sulawesi. The research method used is survey research. Data collection techniques were carried out by observation, interviews, documentation, and questionnaires distributed to respondents, using interview guidelines, questionnaire lists, observation guidelines, and documentation records as data collection instruments. The student population is 181 with a sample of 45 people. The data analysis technique uses descriptive qualitative analysis with a simple percentage formula. From the results of the study, it can be seen that the application of the demonstration method in learning Arabic in Class VIII of Ummul Mukminin Islamic Boarding School of Aisyiyah Junior High School in South Sulawesi was very interesting. It can be seen from the results of the questionnaire that as many as 14 students were highly motivated to learn Arabic with the method used by the teacher or 31.1%, 28 motivated students or 62.2% and 3 unmotivated students or 6.7% with the method used by teacher in the process of learning Arabic.Keywords: Demonstration method, motivation, Arabic